Direct Inhibition of IRF-Dependent Transcriptional Regulatory Mechanisms Associated With Disease - Antonczyk, Aleksandra; Krist, Bart; Sajek, Malgorzata; Michalska, Agata; Piaszyk-Borychowska, Anna; Plens-Galaska, Martyna; Wesoly, Joanna; Bluyssen, Hans A. R. (Frontiers in Immunology, 2019)
Interferon regulatory factors (IRFs) are a family of homologous proteins that regulate the transcription of interferons (IFNs) and interferon-induced gene expression. As such they are important modulating proteins in the Toll-like receptor (TLR) and interferon signaling pathways, which are vital elements of the innate immune system. IRFs have a multi-domain structure, with the N-terminal part acting as a DNA binding domain (DBD) that recognizes a DNA-binding motif similar to the IFN-stimulated response element (ISRE). The C-terminal part contains the IRF-association domain (IAD), with which they can self-associate, bind to IRF family members or interact with other transcription factors. This complex formation is crucial for DNA binding and the commencing of target-gene expression. IRFs bind DNA and exert their activating potential as homo- or heterodimers with other IRFs. Moreover, they can form complexes (e.g. with Signal Transducers and Activators of Transcription, STATs) and collaborate with other co-acting transcription factors such as NF-κB and PU.1. In time, more of these IRF co-activating mechanisms have been discovered, which may play a key role in the pathogenesis of many diseases, such as acute and chronic inflammation, autoimmune diseases and cancer. Detailed knowledge of IRFs structure and activating mechanisms predisposes IRFs as potential targets for inhibition in therapeutic strategies connected to numerous immune system-originated diseases. Until now only indirect IRF modulation has been studied in terms of antiviral response regulation and cancer treatment, using mainly antisense oligonucleotides and siRNA knock-down strategies. However, none of these approaches so far entered clinical trials. Moreover, no direct IRF-inhibitory strategies have been reported. In this review, we summarize current knowledge of the different IRF-mediated transcriptional regulatory mechanisms and how they reflect the diverse functions of IRFs in homeostasis and in TLR and IFN signaling. Moreover, we present IRFs as promising inhibitory targets and propose a novel direct IRF-modulating strategy employing a pipeline approach that combines comparative in silico docking to the IRF-DBD with in vitro validation of IRF inhibition. We hypothesize that our methodology will enable the efficient identification of IRF-specific and pan-IRF inhibitors that can be used for the treatment of IRF-dependent disorders and malignancies.